PELESTARIAN MAKNA BUDAYA-SEJARAH-ALAM LOKAL DALAM ARSITEKTUR PUSAT WISATA GERABAH DESA SITIWINANGUN - CIREBON - Alwin Suryono (Jurnal Arsitektur ARCADE, 2024)
Abstract: This paper aims to identify the architectural plan of Sitiwinangun Village Pottery Tourism Centre from Form-Function elements, then reveal its local cultural-historical-natural meaning, and identify its preservation actions. The method is descriptive-qualitative with the approach of Architecture, Tourism, Culture and Architectural Preservation. The mass-space layout has historical meaning (pottery centre, Islamic propagation), cultural meaning and local nature meaning. Preservation of cultural and historical meaning through the adaptation of the Pottery Centre into a contemporary Pottery Tourism Centre. Preserving the meaning of local nature by maintaining its integration with local nature. The figure of the building open to the local nature means local nature, and its continuity from the Pottery Centre means history. Preservation of the figure of the old building by preservation and regular maintenance, preservation of the new building by maintaining the architectural style of the old building, then preserved. Open building layout-orientation to the old kiln is historically significant. It is preserved by maintaining the principle of open space layout and orientation. The activities of the Pottery Tourism Centre are meaningful to local history, culture and nature. For preservation, the heritage activities are maintained as before, and the present activities are adapted to the demands of the times.Keyword: Form, layout, figure, function, preservationÂ Abstrak: Tulisan ini bertujuan mengidentifikasi rencana arsitektur Pusat Wisata Gerabah Desa Sitiwinangun dari unsur Bentuk - Fungsi, lalu mengungkap makna budaya-sejarah-alam lokalnya, dan mengidentifikasi tindakan pelestariannya. Metodenya deskriptif-kualitatif dengan pendekatan Arsitektur, Pariwisata, Kebudayaan dan Pelestarian Arsitektur. Tata massa-ruangnya bermakna sejarah (Sentra Gerabah, syiar agama Islam), bermakna budaya serta bermakna alam lokal. Pelestarian makna budaya dan sejarah melalui adaptasi Sentra Gerabah menjadi Pusat Wisata Gerabah kekinian, dan pembukaan akses langsung ke masjid Keramat Kebagusan. Pelestarian makna alam lokal dengan mempertahankan integrasinya dengan alam lokal. Sosok bangunan terbuka ke alam setempat bermakna alam lokal, dan keberlanjutannya dari Sentra Gerabah bermakna sejarah. Pelestarian sosok bangunan lama dengan preservasi dan perawatan rutin, pelestarian bangunan baru dengan mempertahankan bergaya arsitektur bangunan lama, lalu dipreservasi. Tata ruang bangunan terbuka-orientasi ke tempat pembakaran lama bermakna sejarah. Pelestariannya dengan mempertahankan prinsip tata ruang terbuka dan orientasinya. Aktivitas Pusat Wisata Gerabah ini bermakna sejarah, budaya dan alam lokal. Pelestariannya, aktivitas warisan dipertahankan seperti semula, dan aktivitas masa kini diadaptasi terhadap tuntutan zaman.Kata Kunci: Bentuk, tata-ruang, sosok, fungsi, preservasi